Pulverized coal-based supported CO2 alcohol amine absorption catalyst as well as preparation method and application thereof

By using a pulverized coal-based supported CO2 alcohol amine absorption catalyst, the problems of low absorption rate and large energy consumption in the CO2 capture process are solved, and efficient CO2 absorption and desorption are achieved, reducing energy consumption and improving the stability of the catalyst.

CN119500146APending Publication Date: 2025-02-25NORTH CHINA ELECTRIC POWER UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411669747.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-21
Publication Date
2025-02-25

AI Technical Summary

Technical Problem

During the CO2 capture process, traditional organic amine solutions have problems such as low absorption rate, large regeneration energy consumption, strong corrosiveness and excessive oxidation and thermal degradation losses.

Method used

The coal-based supported CO2 alcoholamine absorption catalyst is used. The catalyst is prepared by a simple and effective modification method to form a catalyst with a three-dimensional ordered mesoporous structure from modified fly ash as a support and metal oxides such as Fe, Co, Ni as active components.

Benefits of technology

The absorption and desorption amount and efficiency of CO2 are significantly improved, the desorption temperature and energy consumption are reduced, and the catalyst exhibits excellent catalytic activity and stability in the alcohol amine absorption method.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119500146A_ABST
    Figure CN119500146A_ABST
Patent Text Reader

Abstract

The invention discloses a powdered coal-based supported CO2 alcohol amine absorption catalyst and a preparation method and application thereof, the powdered coal-based supported CO2 alcohol amine absorption catalyst comprises a catalyst carrier and an active component, the catalyst carrier is modified fly ash, the active component is at least one of Fe, Co and Ni, and the active component is supported on the catalyst carrier in an oxide form. Compared with the prior art, the catalyst disclosed by the invention is used for capturing CO2 in a 30% MDEA solution, and aims to promote the mass transfer efficiency in the absorption and desorption processes, so that the absorption and desorption amounts of CO2 are increased, and the desorption temperature and energy consumption are reduced. According to the catalyst, fly ash which is low in cost and wide in source is simply and effectively modified, and an FA-AM material with a three-dimensional ordered mesoporous structure is obtained. Subsequently, the active component is further impregnated, which is also ultrasonically treated in order to ensure its payload in the FA-AM. The material shows excellent catalytic activity and stability when CO2 is captured by an alcohol amine absorption method.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of carbon capture technology, in particular to a pulverized coal-based supported CO 2 Alcoholamine absorption catalyst and its preparation method and application. Background Art

[0002] The widespread use of fossil fuels around the world has led to a large amount of CO2 emissions, which has led to an intensified greenhouse effect, causing a series of environmental problems such as global warming, extreme weather, rising sea levels and ecosystem imbalance. In order to reduce the excessively high CO2 concentration in the atmosphere, researchers have proposed many practical solutions, among which carbon capture, utilization and storage technology (CCUS technology) has become the most direct and effective carbon emission reduction technology at home and abroad. 2 Turned into high concentration CO 2 Among them, chemical absorption is one of the most 2 The capture technology is relatively mature. The reason is that traditional organic amine solutions represented by ethanolamine (MEA) / N-methyldiethanolamine (MDEA) have the characteristics of low partial pressure and rapid reaction, and have been industrialized in coal-fired power plants. However, during operation, it was found that organic amine absorbents have problems such as low absorption rate, high regeneration energy consumption, strong corrosiveness, and excessive oxidation and thermal degradation losses. In recent years, in order to solve this problem, catalysts have been added to the solution to improve CO 2 The absorption and desorption properties of α-ketoglutarate have become a promising approach.

[0003] Fly ash (FA) is a large amount of solid waste generated during the combustion process. Its different uses are closely related to its unique physical and chemical properties. These properties are affected by the type of coal from which the fly ash is extracted and the conditions under which it is produced. In general, fly ash has a high specific surface area and exhibits acidic or alkaline characteristics. Its main components are SiO 2 , A 2 O 3 , Fe 2 O 3 Due to the high content of thermally stable metal oxides in fly ash and its easy conversion into porous materials with high surface area, the potential of fly ash in carbon capture, utilization and storage (CCUS) related applications has attracted attention in recent years, especially the material is easy to obtain and cheap because it can be directly obtained from the production process of coal-fired power plants. Therefore, fly ash can be used as a CO2 chemical absorption method. 2 This inexpensive and widely used by-product has shown new potential uses in the present invention. We have systematically studied and evaluated the performance of fly ash as a catalyst and as a catalyst carrier after modification in the absorption performance of amine absorbents and low-temperature desorption processes. Summary of the invention

[0004] In order to solve the above technical problems, the present invention provides a pulverized coal-based supported CO 2 Alcoholamine absorption catalyst and its preparation method and application, in promoting the absorption and desorption of CO by alcoholamine aqueous solution 2 It shows good performance in terms of performance and reducing energy consumption.

[0005] To achieve this technical purpose, the present invention adopts the following scheme: In the first aspect, the present invention provides a pulverized coal-based supported CO 2 The alcohol amine absorbs the catalyst, the catalyst carrier and the active component. The catalyst carrier is modified fly ash, the active component is at least one of Fe, Co and Ni, and the active component is loaded on the catalyst carrier in the form of oxide.

[0006] As a preferred embodiment, the catalyst has a three-dimensional ordered mesoporous structure, and the mass ratio of the active component to the modified fly ash is 1.2-2:10.

[0007] In a second aspect, the present invention provides a pulverized coal-based supported CO 2 The preparation method of the alcoholamine absorption catalyst comprises the following steps: S1. Put the fly ash into an alkaline solution, stir, filter and dry to obtain modified fly ash; S2, dissolving the active component metal salt in deionized water, stirring evenly, adding the modified fly ash therein, stirring, ultrasonicating, and drying; S3. Calcine the dried solid in a muffle furnace and sieve to obtain a catalyst.

[0008] As a preferred option: In step S1, the alkaline solution is NaOH or KOH solution, the concentration is 1-3 mol / L, stirring is performed at room temperature for 12-30 hours, and the drying temperature is 80-100° C. The modified fly ash has a three-dimensional ordered mesoporous structure.

[0009] In step S2, the metal salt is a nitrate or acetate of Fe, Co or Ni, the stirring time is 12 to 24 hours, the ultrasonic time is 0.5 to 1 hour, the drying temperature is 80 to 100° C., and the drying time is 12 to 18 hours. The mass of the metal salt is 20% to 40% of the mass of the modified fly ash.

[0010] In step S3, the calcination temperature is 500-800° C., the calcination time is 3-8 hours, and the sieve used is 100-150 mesh.

[0011] In the third aspect, the pulverized coal-based supported CO 2 Alcoholamine absorption catalyst is used in the alcoholamine solution to promote CO 2The catalyst significantly improves the absorption and desorption process of CO 2 The absorption and desorption amount and efficiency can be improved to achieve the purpose of reducing the desorption temperature and energy consumption.

[0012] Compared with the prior art, the present invention has the following beneficial effects: The present invention relates to a pulverized coal-based catalyst, which is specially used for the CO 2 Capture is designed to improve the mass transfer efficiency during absorption and desorption, thereby increasing CO 2 The catalyst is a FA-AM material with a three-dimensional ordered mesoporous structure, which is obtained by simply and effectively modifying the low-cost and widely available fly ash. Subsequently, the active component is further impregnated, and the FA-AM is also ultrasonically treated to ensure its effective loading in the FA-AM. 2 It exhibits excellent catalytic activity and stability. BRIEF DESCRIPTION OF THE DRAWINGS

[0013] Figure 1 The present invention is a flow chart for preparing the pulverized coal-based catalyst; Figure 2 is the XRD diagram of the pulverized coal-based catalyst of the present invention; Figure 3 The CO of the pulverized coal-based catalyst of the present invention 2 -TPD graph; Figure 4 is the NH 3 -TPD graph; Figure 5 is a PY-IR graph of the pulverized coal-based catalyst of the present invention; Figure 6 is the BET diagram of the pulverized coal-based catalyst of the present invention; Figure 7 TEM image of Ni / FA-AM of the present invention; Figure 8 The pulverized coal-based catalyst of the present invention reacts with CO in a 30% MDEA solution. 2 Absorption performance test result diagram; Fig. 9 The pulverized coal-based catalyst of the present invention reacts with CO in a 30% MDEA solution. 2 Desorption performance test result diagram; Fig.10 The pulverized coal-based catalyst of the present invention reacts with CO in a 30% MDEA solution. 2 The desorption amount and relative energy consumption of desorption; Fig.11 The Ni / FA-AM of the present invention reacts with CO in 30% MDEA solution.2 Absorption-desorption cycle stability diagram; Fig.12 The Ni / FA-AM of the present invention reacts with CO in 30% MDEA. 2 XRD pattern after 5 cycles of absorption and desorption. DETAILED DESCRIPTION

[0014] In order to fully understand the purpose, features and effects of the present invention, the present invention is described in detail through the following specific implementation methods, but the present invention is not limited thereto.

[0015] The present invention provides a pulverized coal-based supported CO 2 The preparation method of the alcoholamine absorption catalyst comprises the following steps: S1. Put fly ash (FA) into an alkaline solution, stir at room temperature for 12-30 hours, filter and dry at 80-100°C to obtain modified fly ash (referred to as FA-AM) with a three-dimensional ordered mesoporous structure. Wherein, the alkaline solution is 1~3 mol / L NaOH or KOH solution.

[0016] The processing method of fly ash (FA) is as follows: weigh an appropriate amount of original fly ash, grind it, pass it through a 120-150 mesh sieve, grind it again and sieve it to obtain FA.

[0017] S2, dissolve the active component metal salt in deionized water, stir evenly, add FA-AM into it, then stir at room temperature for 12-24 hours, ultrasonicate for 0.5-1 hour, and dry at 80-100°C for 12-18 hours; The metal salt is nitrate or acetate of Fe, Co or Ni. The mass of the metal salt is 20% to 25% of the mass of the modified fly ash.

[0018] S3. Calcine the dried solid in a muffle furnace at 500-800° C. for 3-8 hours, and sieve through a 100-150 mesh sieve to obtain a catalyst. Example 1

[0019] In this example, fly ash is alkali-modified. The preparation process is shown in Figure 1 , including the following steps: (1) Weigh 8 g of NaOH and dissolve it in 100 ml of deionized water to a concentration of 2 mol / L.

[0020] (2) After the solution is prepared, 50 g of treated fly ash (FA) is added for modification, and the mass-to-volume ratio of fly ash to solution is 1:2.

[0021] (3) Stir the above solution thoroughly at room temperature for 24 hours.

[0022] (4) Filter the solution and wash it until it becomes neutral, usually 2-3 times.

[0023] (5) Place in oven at 100 o C for 12 h.

[0024] (6) The dried sample is ground and filtered to obtain FA-AM. Example 2

[0025] In this embodiment, fly ash is subjected to alkali modification. The preparation method is similar to that in Embodiment 1, except that the NaOH solution is replaced with a KOH solution. Example 3

[0026] The preparation method of Ni / FA-AM in this embodiment, the preparation process is shown in Figure 1 , including the following steps: Weigh 2.5 g of nickel nitrate and dissolve it in deionized water.

[0027] After the above metal salt is completely dissolved, 7.5 g of FA-AM prepared in Example 1 is added for loading.

[0028] Stir at room temperature for 24 h and sonicate for 1 h.

[0029] After drying at 80 °C for 12 h, the mixture was transferred to a muffle furnace.

[0030] The dried solid was calcined in a muffle furnace at 500° C. for 6 h, and then filtered through a 120-mesh sieve to obtain a catalyst. Example 4

[0031] The preparation method of Fe / FA-AM in this embodiment is similar to that in Embodiment 3, except that nickel nitrate is replaced by iron nitrate. Example 5

[0032] The preparation method of Co / FA-AM in this example is similar to that in Example 3, except that nickel nitrate is replaced by cobalt nitrate. Example 6

[0033] The preparation method of Ni / FA-AM in this embodiment is similar to that in Embodiment 3, except that nickel nitrate is replaced by nickel acetate. Comparative Example 1

[0034] The preparation method of Ni / FA-AM in this example is similar to that in Example 3, except that 7.5 g of FA that has not been treated with alkali is added for loading. Comparative Example 2

[0035] The preparation method of Ni / FA-AM in this example is similar to that in Example 3, except that ultrasonic treatment is not performed when loading the active components.

[0036] The catalyst prepared by the present invention and untreated fly ash FA were systematically characterized and tested for performance, and the specific results are as follows: 1. XRD characterization analysis like Figure 2 As shown, fly ash FA, FA-AM (Example 1), Ni / FA-AM (Example 3) and Fe / FA-AM (Example 4) were characterized. It can be seen that the characteristic peaks of the fly ash-based catalysts are similar, indicating that their crystal compositions are almost the same, mainly mullite and quartz silicon-aluminum phases. By comparing the diffraction peaks of FA and FA-AM, the diffraction peak of FA-AM is slightly reduced. The reason for this phenomenon is that after the fly ash reacts with sodium hydroxide, the crystal structure of mullite, quartz, etc. is destroyed, resulting in concave holes on the surface of the fly ash and the opening of the internal channels. It can be seen from the diffraction pattern that when the carrier is loaded with different active components, the characteristic peaks of the corresponding metal oxides can be well observed. The results show that the metal oxides are well dispersed on the catalyst surface in the form of a crystalline phase. This can be confirmed by observing the lattice fringes of nickel oxide in the TEM image of Ni / FA-AM.

[0037] 2. TPD and PY-IR Characterization Analysis like Figure 3-5 As shown, fly ash FA, FA-AM (Example 1), Ni / FA-AM (Example 3) and Fe / FA-AM (Example 4) were characterized by TPD and PY-IR. It can be seen that FA has very weak acid-base sites, and the powdered coal-based catalyst after modification and loading has good acid-base sites.

[0038] 3. TEM Characterization Analysis Ni / FA-AM (Example 3) was characterized by TEM. Figure 7 It can be seen from a that Ni oxide is highly dispersed on the catalyst surface, which is consistent with the XRD results. In order to more intuitively identify the structure of nickel in the crystalline or amorphous NiOx of fly ash, the morphology of the catalyst was observed by HRTEM. The results are shown in Figure 7 The catalyst Ni / FA-AM shown in d shows obvious void agglomeration and lattice fringes caused by nickel oxide. Therefore, the transmission results allow us to speculate that NiOx is dispersed on the fly ash surface in the form of a crystalline phase. Figure 7 (b, c) The Si and Al in fly ash are also well dispersed on the catalyst surface.

[0039] 4. BET Characterization Analysis The structural properties of pulverized coal-based catalysts were measured by BET. Figure 6 N of FA, FA-AM (Example 1), Ni / FA-AM (Example 3), Co / FA-AM (Example 5) and Fe / FA-AM (Example 4) 2 Adsorption-desorption isotherms. According to the IUPAC classification, all catalysts showed typical type IV isotherms and hysteresis loops were observed at relative pressures of 0.5-1, and the pore sizes were concentrated in the range of 0-5 nm, indicating that the catalysts had a mesoporous structure.

[0040] 5. Effect of pulverized coal-based catalyst on promoting MDEA Prepare a 30wt% ethanolamine (MDEA) solution, add 0.25wt% of the powdered coal-based catalyst in the example, put the solution into a beaker, stir evenly and perform ultrasonic treatment. When the inlet and outlet gas of the instrument are almost the same, pour the liquid into a three-necked flask and turn on the CO 2 The mass flow meter is used for analysis. When the solution is fully absorbed, the mass flow meter is turned off to absorb the fully absorbed CO. 2 The three-necked flask was directly placed in a heated (90°C) desorption water bath, and the mass flow meter was turned on again. After all desorption was completed, the mass flow meter was turned off. The data was processed using origin software.

[0041] In the following tests, the blank group is the control group with MDEA without catalyst. Figures 8-10 shown.

[0042] Depend on Figure 8 It can be seen that FA only slightly promotes the absorption amount and absorption rate. Accompanying base modification and loading different metals on this basis can further improve the catalytic performance, especially loading Ni / FA-AM. Compared with the blank, the absorption amount increased by 8% and the maximum absorption rate increased by 63%. The absorption saturation time was advanced by about 6000s, which means that industrial equipment can be made smaller while capturing the same amount of CO 2 , which will reduce the operating cost of the equipment.

[0043] Depend on Fig. 9 It can be seen that the addition of pulverized coal-based catalyst accelerates the desorption amount and desorption rate. Within 3600s, the desorption amount of the original fly ash increased by 12%, and then the modification and loading of fly ash were found to be further improved, especially the loading of Ni / FA-AM, which increased the desorption amount by 19% and the maximum desorption rate by 10% compared with the blank. Fig.10As shown in the figure, the relative heat load is ranked as Blank (100%) > Co / FA-AM (85%) > FA-AM (82%) > Fe / FA-AM (78%) > Ni / FA-AM (76%). The addition of pulverized coal-based catalyst reduces energy consumption by about 20%.

[0044] 6. Ni / FA-AM cycle The experimental method is similar to the above, except that after the first desorption is completed, the mixture is placed in a cold water bath to cool down, and then the second absorption and desorption experiment is started, which is repeated 5 times.

[0045] The experimental results are as follows Fig.11 As shown in Figure 2, the catalyst exhibits good cyclic stability. After five cycles, the absorption amount decreased slightly, but the desorption amount was still 7.53 gCO 2 / 100g amine, a slight decrease of 9% compared with the first time. The relative heat load gradually increased from 76% to 86%. It only increased by 10%. After 5 cycles of experiments, the Ni / FA-AM catalyst was centrifuged, washed, dried, and XRD and the results were as follows Fig.12 As shown, the results show that the structure and composition of the catalyst have no significant changes, and the loaded metal nickel still exists on the fly ash surface in a divalent form. The content of surface adsorbed oxygen has no significant change. These results show that the catalyst has strong stability in absorption and desorption, and maintains good catalytic activity after 5 cycles.

[0046] Finally, it should be noted that the above are only preferred embodiments of the present invention. Of course, those skilled in the art can make changes and modifications to the present invention. If these modifications and variations fall within the scope of the claims of the present invention and their equivalent technologies, they should be considered to be within the scope of protection of the present invention.

Claims

1. A pulverized coal-based supported CO2 alcohol amine absorption catalyst, a catalyst carrier and an active component, characterized in that: The catalyst carrier is modified fly ash, the active component is at least one of Fe, Co and Ni, and the active component is loaded on the catalyst carrier in the form of oxides.

2. The pulverized coal-based supported CO2 alcoholamine absorption catalyst according to claim 1, characterized in that: The catalyst has a three-dimensional ordered mesoporous structure.

3. The pulverized coal-based supported CO2 alcoholamine absorption catalyst according to claim 1, characterized in that: The mass ratio of active components to modified fly ash is 1.2~2:

10.

4. A method for preparing a pulverized coal-based supported CO2 alcohol amine absorption catalyst, characterized in that: The following steps are involved: S1. Put the fly ash into an alkaline solution, stir, filter and dry to obtain modified fly ash; S2, dissolving the active component metal salt in deionized water, stirring evenly, adding the modified fly ash therein, stirring, ultrasonicating, and drying; S3. Calcine the dried solid in a muffle furnace and sieve to obtain a catalyst.

5. The method for preparing the pulverized coal-based supported CO2 alcoholamine absorption catalyst according to claim 4, characterized in that: In step S1, the alkaline solution is NaOH or KOH solution with a concentration of 1-3 mol / L, stirred at room temperature for 12-30 hours, and the drying temperature is 80-100°C.

6. The method for preparing the pulverized coal-based supported CO2 alcoholamine absorption catalyst according to claim 4, characterized in that: The modified fly ash in step S1 has a three-dimensional ordered mesoporous structure.

7. The method for preparing the pulverized coal-based supported CO2 alcoholamine absorption catalyst according to claim 4, characterized in that: In step S2, the metal salt is nitrate or acetate of Fe, Co or Ni, the stirring time is 12 to 24 hours, the ultrasonic time is 0.5 to 1 hour, the drying temperature is 80 to 100° C., and the drying time is 12 to 18 hours.

8. The method for preparing the pulverized coal-based supported CO2 alcoholamine absorption catalyst according to claim 4, characterized in that: In step S2, the mass of the metal salt is 20% to 40% of the mass of the modified fly ash.

9. The method for preparing a pulverized coal-based supported CO2 alcoholamine absorption catalyst according to claim 4, characterized in that: In step S3, the calcination temperature is 500-800° C., the calcination time is 3-8 hours, and the sieve used is 100-150 mesh.

10. A pulverized coal-based supported CO2 alcoholamine absorption catalyst as claimed in any one of claims 1 to 3, applied to an alcoholamine solution to promote the absorption and desorption of CO2 and reduce energy consumption.